2019
DOI: 10.1039/c9na00171a
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquids to monitor the nano-structuration and the surface functionalization of material electrodes: a proof of concept applied to cobalt oxyhydroxide

Abstract: This paper reports on an innovative and efficient approach based on the use of ionic liquids to govern the nano-structuration of HCoO2, in order to optimize the porosity and enhance the ionic diffusion through the electrode materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…For both materials, the sharp band at ~3629 cm -1 (νOH: stretching of the free hydroxyl groups) and the broad signal peaking at 530 cm -1 attributed to Co-O stretching perfectly fit with to the spectrum of ß-Co(OH)2. 27 For Co(OH)2-IL, the additional signals corresponding to νB-F (~1084 cm -1 ), νC-N (~1569 cm -1 ) and νC-H (between 2900 and 3200 cm -1 ) confirm the presence of EmimBF4 even after several washing steps, 18,28 whereas the low intensity peak at 2425 cm -1 could be attributed to boron-oxygen bonds. These latter might be formed by the reaction between the decomposition products of BF4and the solvent, indeed BF4can be partially decomposed under ultrasonic radiation and generate Fions.…”
mentioning
confidence: 93%
“…For both materials, the sharp band at ~3629 cm -1 (νOH: stretching of the free hydroxyl groups) and the broad signal peaking at 530 cm -1 attributed to Co-O stretching perfectly fit with to the spectrum of ß-Co(OH)2. 27 For Co(OH)2-IL, the additional signals corresponding to νB-F (~1084 cm -1 ), νC-N (~1569 cm -1 ) and νC-H (between 2900 and 3200 cm -1 ) confirm the presence of EmimBF4 even after several washing steps, 18,28 whereas the low intensity peak at 2425 cm -1 could be attributed to boron-oxygen bonds. These latter might be formed by the reaction between the decomposition products of BF4and the solvent, indeed BF4can be partially decomposed under ultrasonic radiation and generate Fions.…”
mentioning
confidence: 93%
“…For instance, it is reported that CoOOH functionalized with BMIMBF 4 ionic liquid exhibits a higher pseudo-capacitive response than pristine CoOOH, although its SSA is lower. 12 surface reactivity of the pseudo-capacitive materials is thus a key point to develop a rational strategy and reach the best energy-storage performance. To this end, we followed a strategy previously used in our group on the investigation of LIB electrode materials that allowed us to get deep insights into the chemical properties of the surface and the electronic processes taking place.…”
Section: ■ Introductionmentioning
confidence: 99%
“…16−19 However, the experimental pseudo-capacitive response of β(III)-cobalt oxyhydroxide, far below the theoretical expectation, leads us to perform a multiscale study to investigate in detail the reactivity of the different surfaces, the nature of the active sites and to identify the mechanisms involved in the charge storage. 8,12 To do this, the adsorption of gas such as SO 2 was carried out to probe the nature of the active sites. X-ray photoelectron spectroscopy (XPS) was used to characterize the surface in terms of electronic structure and composition of the material and also to determine the adsorption mode of SO 2 (redox and/or acid/ base).…”
Section: ■ Introductionmentioning
confidence: 99%
“…32 A surface functionalization involving the grafting of ionic liquid molecules on the materials'surface can also occur during the synthesis step, which can later protect the electrode materials from moisture oxidation, and enhance their electrochemical performance upon cycling by improving their ionic transport properties. [36][37][38][39] In this work, we will investigate the possible use of the ionothermal approach to synthesize the polyanionic compound Na 3 V 2 (PO 4 ) 2 FO 2 (NVPFO 2 ) with an original morphology. The influence of this peculiar morphology on the electrochemical performance of the as-obtained material will also be studied in detail.…”
Section: Introductionmentioning
confidence: 99%